Seasonality chart of underutilized fruits found in the Eastern Himalayas - Angami, Thejangulie; Wangchu, L (Indian Horticulture, 2021)
Nature in its generous abundance has bestowed the Eastern Himalayan region with a unique array of vegetation ranging from tropical and sub-tropical to temperate. The region has varied agro-climatic conditions supporting the growth of various plant species giving it a rich biological diversity. The article reports on the documentation of wild underutilized edible fruits species found in the entire region of North east India and its thorough observation on the time of flowering and fruit availability or fruit maturity which is paramount. A total of 44 underutilized fruit species represented by 21 families were listed and sampled from varied locations of the region in which Rosaceae family represented the highest with 6 species. Developing a seasonality chart or calendar will identify the timing of different seasons for locally available fruit species. The chart can also be used as a guide to explore different underutilized fruits throughout the year.